The development of our sense of self as a defense against invading thoughts: from Buddhist psychology to psychoanalysis - Mayer, Andreas Frank (New ideas in psychology, 2020)
In interdisciplinary debates on the nature of the self, no-self accounts often refer to Buddhist psychology, arguing that the self is an illusion arising from our identification with mental content. What is often missing, however, is a developmentally, motivationally and emotionally plausible reason why this identification happens in the first place. It is argued that directing attention to our ongoing thought activities and their effect on our mind reveals their often invasive character. This is supported by psychoanalytic accounts on the ontogenetic and phylogenetic origins of thinking. On an experiential level, invading thoughts have similarities to attacks and provoke defensive reactions. The defense mechanism described as identification with the aggressor is used as a model in order to better grasp how we deal with invading thoughts, namely, by identifying with them and thus generating a sense of self as an agent of thoughts which provides an illusion of control.
Available online 9 December 2019
Gesehen am 13.07.2020